Capturing the Complexity of Malleable IT Use: Adaptive Structuration Theory for Individuals1 - Schmitz, Kurt W.; Teng, James T. C.; Webb, Kimberly J. (MIS Quarterly, 2016)
The confluence of widely available malleable technology and the “bring your own device” (BYOD) trend creates a new dynamic for information technology innovation in the workplace. Nontechnical users are empowered to adapt pliable technology in the course of normal usage episodes. We develop a theoretical perspective of adaptation behaviors by extending the adaptive structuration theory (AST) to the level of individuals, and present a topology of adaptation behaviors to capture the rich landscape of this emerging phenomenon. Based on this new theoretical perspective, we propose a research model and perform a survey study targeting young professionals to empirically investigate adaptation of malleable IT by users. Our findings reveal the compounding effects of four distinct adaptation behaviors including the insight that task adaptation mediates the effect of technology adaptation on individual performance. This study contributes by providing a theoretical framework for examining adaptation behaviors, extending AST to the level of individuals, and addressing specific criticisms of AST in the information systems literature.